Freeze Dryer Machine Design for Mango Fruit Storage - Wardika; Aa Setiawan; Sandi Rifqi Ridwansyah (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
The purpose of the research on the design of this tool is to determine the cooling load on the freeze dryer and to determine the time it takes to reach a temperature of -20°C. This tool uses a vapor compression cooling system and a vacuum process means that this tool cools the storage space with air in the dry cabin. The research method is to determine the volume of the cabin to determine the capacity of the freeze dryer and determine the cooling load by calculating the product load and then calculating the heat load through the walls and other loads that generate heat. for a freeze dryer machine with a capacity of 1.8 PK. From testing the tool for 10 minutes once for 6 hours, the results of the system performance at the evaporator temperature -24.64°C and product temperature -16.2°C, COPCarnot performance of 3.77, and COPAktual of 2.87 with an efficiency of 76%, This is in line with the performance values ​​in the COPCarnot design of 3.8 and COPActual of 3.30 with an efficiency of 87%.